La nouvelle histoire atlantique en France : Ignorance, réticence et reconnaissance tardive - Cécile Vidal (Nuevo mundo - Mundos Nuevos, 2008)
This essay addresses the reception in France of the new Atlantic history, which originated in the United States during the past two decades. It seeks to explain the intellectual, institutional, political, and cultural reasons behind French academic resistance towards this new historiographical current, focusing on two main factors: the « crisis » faced by the French historical school, and the non-integration of colonization and slavery into French collective history and memory. The paper then demonstrates how this historiographical context has particularly affected the writing of early modern colonial history. Finally, it presents recent initiatives which have contributed to the diffusion of the new Atlantic history in France.